Evaluación del riesgo de pérdida auditiva por causa laboral e implementación de un programa de conservación auditiva en la empresa Ekador S.A. - Andrade Ruíz, Carlos Olmedo (2009)
Along the present work, the reader will find a lot of theoretical precisions that will lead him to fully understand the importance of the Noise is Control inside the wide field of the Occupational Health. Likewise, the necessary orientation will be provided to understand the problems provoked in the environment of companies where every day the factor noise is immersed, its reasons, possible consequences in the general health and actions to tackle its control and for the preservation of the audition health of the workers. It is important to anticipate that the present study ends in a specific Program of Audition Conservation for the company Enkador S.A., and it is raised as result of a systematic investigation of field and then an analysis of the work areas; similar studies always will need technical assistance to reach results that they should adjust to the needs of the personnel and employers. Though the evaluated company presents acceptable conditions of noise levels, there is necessary the application of certain measures that prevent, in the future, the increase of the risk of audition loss in the workers, overcoat, in those that work in areas of high and risky noise levels; and of some other measures of immediate application that regulate the noise in the environment in order to adjust it in relation to the in force regulation.